2009
DOI: 10.1097/prs.0b013e3181b988aa
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Breast Reduction Surgery on Low-Back Compressive Forces and Function in Individuals with Macromastia

Abstract: Reduction mammaplasty surgery produced objective improvement in low-back compressive forces and patients' reported level of functional disability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 30 publications
0
28
0
1
Order By: Relevance
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] Common complaints include back pain, shoulder pain, neck pain, bra-strap grooving, and intertrigo under the breasts. The benefits of reduction mammaplasty include the increased ability to exercise, 12 improved quality-of-life outcomes, and overall satisfaction with breast contour.…”
mentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] Common complaints include back pain, shoulder pain, neck pain, bra-strap grooving, and intertrigo under the breasts. The benefits of reduction mammaplasty include the increased ability to exercise, 12 improved quality-of-life outcomes, and overall satisfaction with breast contour.…”
mentioning
confidence: 99%
“…Furthermore, pain, decreased stamina, emotional response disorders, sleep and socialization disorders, physical disabilities, and intensity of depressive symptoms were not investigated in that study. Karabekmez et al [24] reported a preoperative increase of cervical lordosis and thoracic kyphosis angles in all patients and a significant decrease of the aforementioned angles in the postoperative period. In their study, lumbar lordosis decreased in seven patients and increased in eight patients, and the preoperative total breast volume was correlated with the BMI and thoracic kyphosis angle.…”
Section: Discussionmentioning
confidence: 97%
“…In our study, the resected breast tissue per breast ranged between a minimum of 362.5 g and a maximum of 1900 g. Based on our clinical experience, a breast tissue weight of 600 g on the thoracic wall may affect the vertebral angles, but this needs to be validated by further investigations. A biomechanical study showed the improvement of symptoms in terms of pain frequency and irradiation after reduction mammaplasty to reduce the low-back compressive forces [24]. In another study, an improvement in body posture was achieved because of the reestablishment of the body's center of gravity after reduction mammaplasty [25].…”
Section: Discussionmentioning
confidence: 98%
“…The main indications of reduction mammaplasty for patients with Gigantomastia range from improving the shape of the breasts to somatic symptoms. There are several associated symptoms in the breast and musculoskeletal system (back, shoulder and cervical spine) 1,2 . Several retrospective and prospective studies have documented statistically significant improvement in symptoms and quality of life of patients who underwent reduction mammaplasty [3][4][5][6] .…”
Section: Introduction Introduction Introduction Introduction Introducmentioning
confidence: 99%